Presenting Clinico-laboratory Characteristics, Hospital Course and Outcomes of Admitted Children with COVID19 in a Tertiary Pediatric Hospital of Nepal - Chapagain, Ram Hari; Adhikari, Santosh; Pokharel, Sunita; Shrestha, Susan Man; Bichha, Ram Padarth (Journal of Nepal Health Research Council, 2021)
Background: COVID-19 pandemic hit all age group with different presentations and outcome. This study aimed at exploring the clinical characteristics, investigational findings, hospital outcome along with 90 days follow up of COVID-19 infection in children. Methods: This was longitudinal descriptive study among hospital admitted children with COVID-19 RT-PCR positive during first wave of Pandemic with 90 days telephonic follow up. Demographic and clinical characteristics, comorbidities, SPO2, investigations, need of oxygen , PICU admission, need of ventilator, outcome (improved and discharged, death) and duration of hospital stay were recorded and 90 days telephonic follow up was performed for any illness and hospital admission. Results: Out of 65 children admitted, male 44 (67.7%) and female 21 (32.3%), median age was 23 months ( IQR 6 days -14 years) with 52( 80.0%) without any comorbid conditions. The common signs were Fever 40(61.5%) vomiting 15 (23.1%) and Cough 11(16.9%).Thirteen (20.0%) children has platelets count less than 150000 and 16(24.6%) had C - reactive protein Positive .Mean duration of hospital stay 8 days (Range 1 -44 days), 20( 30.8% ) needed oxygen , 20(30.8%) needed Pediatric intensive care unit (PICU)admission and 6 (9.2%), needed ventilator. Forty seven (72.3%) recovered and discharged with death of 6.2% (n=4). Fifty six children (75.4%) has not experienced any problem after COVID -19 and only 2 children needed hospital admission in 90 days telephone follow up. Conclusions: In the first wave of the pandemic, Respiratory and Gastrointestinal symptoms were common presentation with few Severe and critical cases. Majority had good outcome. Majority has no other related illness till 90 days after discharge. Keywords: Children;COVID-19; follow up; hospital outcome; sign symptoms